Analisis Kebangkrutan dengan Menggunakan Metode Altman Z-score Springate dan Zmijewski pada Perusahaan Semen yang Terdaftar di BEI Periode 2011-2015 - Susanti, Neneng (Jurnal Aplikasi Manajemen, 2016)
Bankruptcy is a condition which is avoided by the entire company. One way to avoid bankruptcy is to identify it early or as soon as possible. Require an analysis of bankruptcy, so that firms can know with certainty the condition of the company and can take the right decision for the sustainability of the company. There are several methods that can be used to analyze the bankruptcy, the method used in this research is the Altman Z-Score, Springate and Zmijewski. Objects of this study was cement companies listed on the Stock Exchange 2011-2015 period. The results revealed that the company went bankrupt SMCB detected by the Altman Z-Score and Springate, while the method of Zmijewski explained that the three companies are healthy or avoid bankruptcy. Kruskal Wallis test results showed that there was no significant difference between the three methods used because it has a significance value of 0.351 that is> 0.05.